Elevated Driving Pressure and Elastance Does Not Increase In-Hospital Mortality Among Obese and Severely Obese Patients With Ventilator Dependent Respiratory Failure. (12th December 2022) - Terry, Charles; Brinton, Daniel; Simpson, Annie N.; Kirchoff, Katie; Files, D. Clark; Carter, George; Ford, Dee W.; Goodwin, Andrew J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Importance: Existing recommendations for mechanical ventilation are based on studies that under-sampled or excluded obese and severely obese individuals. Objective: To determine if driving pressure (DP) and total respiratory system elastance (Ers ) differ among normal/overweight (body mass index [BMI] < 30 kg/m 2 ), obese, and severely obese ventilator-dependent respiratory failure (VDRF) patients and if there any associations with clinical outcomes. Design, Setting, and Participants: Retrospective observational cohort study during 2016–2018 at two tertiary care academic medical centers using electronic health record data from the first 2 full days of mechanical ventilation. The cohort was stratified by BMI classes to measure median DP, time-weighted mean tidal volume, plateau pressure, and Ers for each BMI class. Setting and Participants: Mechanically ventilated patients in medical and surgical ICUs. Main Outcomes and Measures: Primary outcome and effect measures included relative risk of in-hospital mortality, ventilator-free days, ICU length of stay, and hospital length of stay with multivariable adjustment. Results: The cohort included 3, 204 patients with 976 (30.4%) and 382 (11.9%) obese and severely obese patients, respectively. Severe obesity was associated with a DP greater than or equal to 15 cm H2 O (relative risk [RR], 1.51 [95% CI, 1.26–1.82]) and Ers greater than or equal to 2 cm H2 O/(mL/kg) (RR, 1.31 [95% CI, 1.14–1.49]). Despite elevated DP and Ers, there were no differences in in-hospital mortality, ventilator-free days, or ICU length of stay among all three groups. Conclusions and Relevance: Despite higher DP and ERS among obese and severely obese VDRF patients, there were no differences in in-hospital mortality or duration of mechanical ventilation, suggesting that DP has less prognostic value in obese and severely obese VDRF patients.